The association between salivary amylase gene copy number and enzyme activity with type 2 diabetes status. - Sri Lakshmi Sravani Devarakonda; Jennifer Ren; Angela C Poole (PLoS ONE)
The association between salivary amylase gene (AMY1) copy number (CN) and metabolic health parameters, such as insulin resistance, has been studied but with conflicting results. The etiology of these inconsistencies is multifaceted and confounded by differences in genotyping methods. In this study, we investigated the factors that affect the association between AMY1 CN, salivary amylase activity (SAA), and type 2 diabetes (T2D) status. We collected up to four saliva samples from two cohorts: individuals with self-reported T2D or prediabetes (n = 18) and individuals who self-reported as being without T2D or prediabetes (controls, n = 178). We genotyped individuals for AMY1 CN using both quantitative PCR and droplet digital PCR and measured SAA in the saliva samples. We demonstrated that these two commonly used methods give comparable values for AMY1 CN. We showed a positive association between the time of saliva collection and SAA throughout the day. We also observed that AMY1 CN and SAA are positively associated in individuals with and without T2D or prediabetes. With increasing AMY1 CN, SAA was higher for each additional copy of AMY1 CN in individuals with T2D or prediabetes compared to controls. Our findings support the premise that increased SAA in T2D patients is a compensatory mechanism related to the long-term protective effect of high AMY1 CN on glucose metabolism.